Differences in the Parsing of the Present Tense Verb in Qur’anic Verses in Order to Develop Arabic Language Skill - Huda, M. Nurul; Holilulloh, Andi; Mustaqim, Abdul; Patah, Akhmad; Ahmed, Essam Mustafa (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This research aims to expose the meanings, and the difference in the structure of the present tense in the frequent Qur’anic readings with an explanation of the impact of this difference in the noble verse, and it aims to provide correct linguistic models that contribute to building the linguistic ability of the students. The methodology was followed in this research, and this research included an introduction, a methodology section, result and discussion, and the last is conclusion. As for the introduction, it defined the subject of the research, the reasons for its selection, its objectives, the method used, the basic rule, previous studies, and the study plan. It focuses on linguistic analogy, meaning of harf jarr, linguistic skills, its definition and methods of obtaining. The present tense verb is preceded by harf lām and atf that considering the lām as a reasoning. It is not a condition for the present tense to be in the accusative case that the lam be clear in its reasoning. The lam and atf has function in the present tense verb “to be made” was read with the kasra of the lam and the accusative, and with the sukun of the lam and the jazm in the context of al-fi’l al-mudhari’, and it is clear that the reading of the kasra of the lam and the accusative was directed by considering the lam for the reasoning and the accusative of “to be made” with (that) is implicitly permissible.